Accelerometer Measurements of Water Rocket Motion - Cao, Junbin (My University, 2012)
The purpose of this study was to use accelerometers and micro-controllers to measure the acceleration of water rockets and to compare the results to a theoretical model developed by Peter Nielsen of the University of Queensland.
Color poster with images and graphs.
Keywords: Accelerometers; Acceleration (Mechanics)--Measurement; Rocketry; Posters